(untitled) (World Bulletin of Education and Learning, 2026)
This article examines the theoretical and practical foundations of personnel-cost management in modern organizations. The study analyzes the economic nature, structure, classification, and strategic significance of labor-related expenditures within contemporary management systems. Particular attention is devoted to direct labor costs, social-security expenditures, professional training investments, compensation systems, workplace-support expenses, and human-capital-development mechanisms. The research applies analytical, comparative, systemic, and organizational-economic approaches to evaluate the relationship between personnel costs and organizational efficiency. Research findings demonstrate that modern enterprises increasingly interpret personnel expenditures not merely as operational costs but as long-term strategic investments capable of generating sustainable competitive advantages. The article further explores the transformation of workforce-cost management under conditions of digitalization, globalization, and knowledge-based economic development.